Evil must not have the last word : the life of Mary Wygodski ; Holocaust survivor, mother, teacher, & witness - Burke, Tom J. (Veteranscribe Press, 2021)
"Mary Wygodski lost her entire immediate family to the Nazi death machine. Spared for slave labor, she survived three concentration camps, narrowly escaping death many times. She made her way to Palestine, where she met her husband and took part in Israel's War of Independence. After moving to America to raise her family, Mary could not remain silent about what had happened to her. She heard the denials and dismissals of the Holocaust, and she had to speak out. She overcame her initial shyness and reluctance, and has dedicated the rest of her life to speaking the truth about the Holocaust."--Amazon.com